LINGUISTICS OF COLOR-DENOTING ADJECTIVES IN MODERN UZBEK POETRY - Nishonova Adiba Adhamjon qizi (American Journals, 2023)
In this article, the linguopoetics of color-denoting adjectives in modern Uzbek poetry is analyzed. The article talks about the essence of the concept of linguopoetics found in Uzbek linguistics today. The evaluation of linguopoetics in Uzbek and world linguistics, different approaches to this phenomenon and scientific works are discussed. This scientific article talks about the essence of the concept of theoretical issues of linguopoetics in Uzbek and world linguistics. The evaluation of linguopoetics in Uzbek and world linguistics, various approaches to this phenomenon, scientific works, and qualities that give color in modern Uzbek poetry are discussed. [1]
Keywords: The concept of linguopoetics, the study object and subject of linguopoetics, goals and tasks, the history of researches related to linguopoetics and types of analysis are shown, cognitive linguistics, linguopoetic analysis of adjectives.